Assessment on gadgets addiction and its relation to sexual addiction behavior among undergraduate students - Ahmad, Roslee; Hassan, Mohamad Syafiq; Yusoff, 3Mohd Nasir Che Mohd; Sawai, Rezki Perdani; Mahyuddin, Muhamad Khairi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the gadgets addiction and sexual addiction behaviour among undergraduate students in one of public university in Malaysia. This study was conducted among 201 students consist of 94 male adolescents and 107 female adolescents from random sample selection. Their ages range were 23-25 years old from 3 different programs. The instruments were adapted from The Internet Addiction Test created by Young (1998) and Psychosocial and Individual Compulsive Sexual Behavior created by Efrati and Mikulincer (2018) with reliability Cronbach alpha of 0.65. Data collected were analyzed using Statistical Package for Social Science (SPSS) version 23. Statistic descriptive and inferential with analysis t-test and correlation Pearson were used to analyse the data. Results showed there is significant different between gadgets addiction behaviour among adolescents based on gender but no significant different between sexual addiction behaviour among them. Finding also showed a negative correlation between gadgets addiction and sexual addiction behavior among adolescents. This indicates that the effect of gadgets addiction toward sexual addiction behavior is in moderate level. Researcher believe there are other factors such as peers influence, environment factors and maturity of ages plays a significant variables that lead adolescents to involve in this misbehaviour problems. Researcher also recommends in future studies to get a larger sample across multiethnic and culture, parents background, level of education and status socioeconomic factor should be considered as significant variables to gain better findings.